Towards a physically informed understanding of new particle formation and growth in the atmosphere - O'Donnell, Samuel Emmart, author; Pierce, Jeffrey R., advisor; Jathar, Shantanu H., committee member; Kreidenweis, Sonia M., committee member; Fischer, Emily V., committee member (Colorado State University. Libraries, 2025)
Aerosol particles are among the most uncertain yet influential components of Earth's radiative balance, influencing it directly through interactions with radiation and indirectly by serving as the formation sites for cloud droplets and ice crystals. Understanding the size and composition of the aerosol particles is critical for understanding their climate impacts. The majority of aerosol particles in the atmosphere form through the process of new particle formation and growth (NPF&G), the process by which new small particles form from the clustering of low-volatility vapors. These newly formed particles may grow to climatically relevant sizes through condensation of vapors or be lost through collisions with pre-existing larger particles. NPF&G events are time periods where NPF&G occurs, and the particles grow substantially over the following several hours. This dissertation examines the processes governing NPF&G in the atmosphere. First, we investigate the implications of stationary-site observations of NPF&G events by contrasting them with a Lagrangian perspective. Most observations of NPF&G events are conducted at stationary sites; however, NPF&G observed from stationary sites is influenced by gradual or rapid changes in the air masses passing over the site, complicating NPF&G analysis. In this work, we use observations and a 3D aerosol model to compare aerosol size distributions at a stationary site (Southern Great Plains (SGP) observatory, Oklahoma, USA) and along Lagrangian trajectories crossing the site. The model simulates the NPF&G events reasonably well compared to observations at SGP. Using the model to compare the Lagrangian and stationary perspectives, we can explain previously unanalyzable days with some evidence of NPF&G as either non-event or analyzable NPF&G days. We find most of the unanalyzable NPF&G days are due to isolated and inhomogeneous NPF&G occurring upwind of the stationary site, often in the outflow of urban regions. Finally, we compare formation rates of 3 nm particles, growth rates, and the survival probability of 3 nm particles growing to 25 nm between the stationary and Lagrangian perspectives. Due to the much larger number of analyzable days along the Lagrangian trajectories, this perspective potentially provides more robust statistics and better characterization of NPF&G event extremes. Our method for extracting chemical/physical properties along Lagrangian trajectories from 3D models can be applied to a wide range of science questions. Second, to better understand NPF&G in urban environments, we examine NPF&G occurring in a unique environmental chamber. While our understanding of NPF&G in certain environments has advanced, the processes that govern NPF&G in some urban environments are still poorly understood. As part of the Tracking Aerosol Convection Interactions Experiment (TRACER) Ultrafine Aerosol Formation and Impacts (UFI; together TRACER-UFI) campaign, the University of California, Riverside's Captive Aerosol Growth and Evolution (CAGE) chamber operated during July and August of 2022. The CAGE chamber filters out ambient particles, allowing only ambient vapors to enter. On most days during TRACER-UFI, NPF&G events occurred in the chamber, providing the unique opportunity to assess what chemical species and mechanisms have the potential to drive secondary aerosol processes in Houston. In this work, we use the SOM-TOMAS chemistry and aerosol-microphysics model to represent the CAGE chamber to better understand the governing processes within it. We calculate that aerosol mass in the chamber is primarily derived from toluene, trimethylbenzene, styrene, and monoterpene products. Aerosol measurements in the chamber corroborate the contribution of anthropogenic species to aerosol particles; however, because of challenges of simulating the unique particle and vapor loss mechanisms in the chamber (wall losses, instrument flows, diffusional membrane), other conclusions are less robust. Finally, we examine the effects of particle phase state (i.e., liquid or solid) on the global size-dependent condensation and growth of aerosol particles. The phase state of atmospheric aerosol particles ranges from liquid-like to solid-like, which can profoundly affect size-dependent secondary organic aerosol (SOA) partitioning. In this work, we examine some of the effects of phase state and size-dependent SOA condensation on aerosol size distributions, with a specific focus on NPF&G events. To this end, we use the 3D chemical transport model, GEOS-Chem with the TwO-Moment Aerosol Sectional (TOMAS) microphysics module to test the size-distribution effects from including an updated phase-state-dependent SOA condensation scheme that depends on humidity, temperature, and aerosol composition. Compared to a liquid-like-aerosol assumption, using the phase-state scheme shows a global decrease in the surface number concentration of 3-20 nm particles, likely due to faster growth and increased survival of small particles growing to larger sizes, which consequently hinders further new particle formation (NPF). We find increases in the number concentrations of 20-80 and 80-200 nm particles, with the largest increases occurring in low-relative-humidity regions where particles are more solid-like. Zonally averaged changes in the number concentration of particles mirror the changes at the surface, but the greatest changes are in regions of large-scale subsidence, which generally have low relative humidity. We also investigate regional changes over the south-central United States, where, again, we see the greatest changes in number concentration in dry, cool regions. Finally, we compare average size distributions between the model and several observational datasets, and we highlight several NPF&G event case studies from the Southern Great Plains (SGP) observatory, where the inclusion of size-dependent SOA condensation in the model led to better model-measurement agreement. This work provides novel insights into the global, regional, and site-specific impacts of phase state on size-dependent SOA condensation and aerosol size distributions.
Keywords: new particle formation; aerosol